A systematic review and meta-analysis of the diagnostic accuracy of the spot urinary protein creatinine ratio (PCR) and the spot urinary albumin creatinine ratio (ACR) in the management of suspected pre-eclampsia. (7th June 2011) - Morris, R K; Doug, M; Kilby, M D
Abstract : Objective: To determine the diagnostic accuracy of the albumin creatinine ratio (ACR) and protein creatinine ratio (PCR) compared to the 24 h total urine (24 h TU) and how well they predict adverse outcomes for mother and baby in women with suspected pre-eclampsia (PE). Methods: Systematic searches in electronic databases, reference lists and contact with experts. All studies reporting on ACR and/or PCR in hypertensive pregnant women with suspected PE compared to 24 h TU or to predict adverse outcome and with data for a 2×2 table. No language restrictions. Bivariate meta-analysis was conducted. Results: 3111 citations were identified, 103 papers for detailed evaluation. 20 papers were included in the review, 2978 women. 15 studies examined the PCR compared to 24 hTU, 4 looked at ACR compared to 24 hTU and one at ACR compared to adverse outcomes. A PCR of 0.3 had a sensitivity of 0.93 (95% CI 0.85 to 0.97) and specificity of 0.90 (95%CI 0.71 to 0.97) to predict significant proteinuria on 24 hTU (>0.3 g/day). For ACR meta-analysis was not possible due to different thresholds and study characteristics. Thus the results from one of the studies in a hypertensive pregnant population were sensitivity 0.94 (95% CI 0.85 to 0.98) and specificity 0.94 (95% CI 0.88 to 0.94). Conclusion: The results suggest that PCR and in particular, ACR, may be valuable point of care tests in the management of suspected PE. Further work needs to be performed to look at their role in the management of this condition in the prediction of adverse outcomes for mother and baby and which is the most cost-effective threshold to use.